Ischemical Problems after Filler Injections: Anatomical Details and Practical Guide Lines to Avoid Disasters - Redaelli Alessio; Battistella Melania; Aleksey A Ivanov (Archives of Anatomy and Physiology - Peertechz Publications, 2017)
Introduction: Soft-tissue filler injection is a very common procedure all around the world. Although the safety profile for these products is favorable, adverse events can occur, ranging from mild to severe in intensity. The most disastrous complication reported is accidental intra-arterial filler injection or in rare case due to the compression of the vessel associated with tissue injury and necrosis. Objectives: The authors performed a literature search to identify the facial sites most prone to severe complications, especially due to anatomical structure. After a review of these complications they discuss preventive measures in order to avoid ischemical problems after filler injections and try to give a prompt intervention guidelines to manage this kind of complication and significantly decrease the risk of long term sequelae. Method: The National Library of Medicine, the Cochrane Library, and Ovid MEDLINE were searched, and relevant articles were retrieved based on specific criteria. The complications reviewed included soft-tissue necrosis, filler embolization and visual impairment. Results: Data collected from these case reports showed that the most common injection sites for necrosis are the glabella, the nose and the nasolabial fold. Blindness was most often associated with injection of the glabella. A thorough understanding of the facial vascular anatomy and a good injection technique reduce the risk of vascular occlusion. Conclusions: Although soft-tissue fillers are a popular choice for minimally invasive rejuvenation of the face, physicians should be aware of the serious potential ischemical adverse event risks by using a correct technique of injection based on a good knowledge of anatomy and good instruments trying to prevent and/or manage its.